(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
Although historians of traditional Southeast Asian cultures rely primarily on written sources, the societies they study were intensely oral and aural. Research on sound in Southeast Asia has focused on music and musicology, but historians are now considering the wide variety of noises to which people were exposed, and how the interpretations and understanding of these sounds shaped human experience. This article uses an 1899 court case in Singapore concerning a noisy neighbour as a departure point to consider some of the ways in which “noise” was heard in traditional Southeast Asian societies. Focusing on Singapore, it shows that European attitudes influenced the attitudes of the colonial administration towards loud noise, especially in the streets. By the late 19th century, the view that sleep was necessary for good health, and that noise interfered with sleep, was well established. The changing soundscape of Singapore in the early 20th century led to increasing middle class demands for government action to limit urban noise, although these were largely ineffective. The regulations and public campaigns introduced over the last 60 years still face the problem of intrusive noise, both in the public and private domain. The richness of the Singapore material, only some of which has been consulted for this paper, suggests that the Southeast Asian region has the potential to make a significant contribution to the field of sensory history.